STRUKTUR ANATOMI KAYU YANG DIPERDAGANGKAN DI KABUPATEN ACEH BESAR - Ghozali, Rahmad; Susdiyanti, Tun; Meiganati, Kustin Bintani; Krisdianto, Krisdianto (Universitas Nusa Bangsa, 2022)
This study aims to determine the anatomical structure of wood and its possiblity uses for trade in Aceh Besar District. The research was carried out by observing 13 wood samples from the Bogorience 1915 xylarium wood collection. The observed samples included macroscopic and microscopic characteristics. Macroscopic characteristics include texture, color, pattern, texture, and grain direction of the wood. Microscopic characteristics observed were growth circumference boundaries, vessels, pores, dots, and radii based on the International Association of Wood Anatomists (IAWA) book. Each preparation was observed using a microscope and analyzed descriptively. The results showed that the anatomical structures of the macroscopic and microscopic properties of the 13 Aceh Besar wood species varied in terms of texture, grain direction, radius size, crystal type, fiber length, vessel length, and fiber wall thickness. While the pattern, color, distribution of pores, type of dots, type of perforation area, type of parenchyma cells, and the composition of the cells composing the radius show uniformity, and two kinds of wood have prismatic crystals, namely Surian wood in upright cells and Bangkirai wood in straight cells lie down. The 13 types of wood, 46% include strong class I-II for construction, bridges, pillars, and floors. Meanwhile, 54% is classified as strong class III-V as a material for making furniture, doors, windows, and products that do not require heavy strength.